Comparison of EEG propagation speeds under emotional stimuli on smartphone between the different anxiety states - Asakawa, Tetsuya; Muramatsu, Ayumi; Hayashi, Takuto; Urata, Tatsuya; Taya, Masato; Mizuno-Matsumoto, Yuko (Frontiers in Human Neuroscience, 2014)
The current study was evaluated difference anxiety states at information processing in the electroencephalography (EEG) under emotional stimuli for smartphone. Twenty-three healthy subjects were assessed for their anxiety states using The State Trait Anxiety Inventory (STAI) and divided to two groups: low anxiety (I, II) or high anxiety (III and IV, V) group. EEG was measured under emotionally audio-visual stimuli (resting and pleasant, unpleasant sessions) and emotionally sentence stimuli (pleasant sentence, unpleasant sentence sessions) using emotionally audio-visual stimuli and emotionally sentence stimuli and analyzed using propagation speed analysis. The propagation speed of the low anxiety group at medial coronal in resting stimuli for all time was higher than those of high anxiety group, and that of the low anxiety group at medial sagittal in unpleasant stimuli for 60-150 seconds and those in unpleasant stimuli for 0-30, 60-150 seconds was higher than those of high anxiety group. The propagation speed for 150 seconds of all stimuli in the low anxiety group had a significantly higher than propagation speed for that in the high anxiety group. These events suggest that information processes concerning the emotional stimuli in the brain is differ based on the anxiety state of the subject.